2016
DOI: 10.2147/ijwh.s124229
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ovarian endometrioma on uterine and ovarian blood flow in infertile women

Abstract: BackgroundAngiogenesis has been found to be among the most important factors in the pathogenesis of endometriosis. The formation of new blood vessels is critical for the survival of newly implanted endometriotic foci. The use of 3-D power Doppler allows for the demonstration of the dynamic vascular changes that occur during the process of in vitro fertilization (IVF). We aimed to evaluate the effect of ovarian endometrioma on uterine and ovarian blood flow in infertile women.Materials and methodsIn a case–cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Diminished ovarian volume and low number of antral follicles of 2-10 mm are indications of ovarian maturing that might be noticed sooner than an ascent in FSH focuses. Akmal El-Mazny et al led an examination in 2016 his exploration exhibit the ovarian artery PI in benchmark group was 1.6±0.4 and RI 0.85±0.11 in ordinary ripe females, their outcomes showed that there were no critical contrasts seen in the ovarian Doppler files between endometrioma-containing ovaries and contralateral ovaries 22 . Steer et al, showed that expanded uterine corridor blood stream obstruction can cause unexplained infertility 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Diminished ovarian volume and low number of antral follicles of 2-10 mm are indications of ovarian maturing that might be noticed sooner than an ascent in FSH focuses. Akmal El-Mazny et al led an examination in 2016 his exploration exhibit the ovarian artery PI in benchmark group was 1.6±0.4 and RI 0.85±0.11 in ordinary ripe females, their outcomes showed that there were no critical contrasts seen in the ovarian Doppler files between endometrioma-containing ovaries and contralateral ovaries 22 . Steer et al, showed that expanded uterine corridor blood stream obstruction can cause unexplained infertility 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Mostly attention is paid to changes of sizes and structure of internal genital organs by ultrasound echography. But it ought to re-member that forming of endometrioid foci commonly begins from development of new blood vessels [6]. So, changes of hemodynamics in vessels that can be determined by Doppler are important for complete diagnosis of endometriosis.…”
Section: в д воробийmentioning
confidence: 99%
“…Typically in more than 80% of cases, they appear as a thick walled ovarian cyst containing homogenous "ground-glass" content with no internal vascularity [5,12] . Endometriomata maybe unilateral or bilateral; uni-or multilocular, sometimes single or multiple, and usually more commonon the left side [13] .…”
Section: Introductionmentioning
confidence: 99%